2018
DOI: 10.1097/wnp.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcranial Motor Evoked Potential Amplitude Responses Between Intramuscular and Subcutaneous Needles in Proximal Thigh Muscle

Abstract: Higher TcMEP amplitude responses are seen with longer needles compared with shorter needles placed in the same rectus femoris muscle. Transcranial motor evoked potential baselines may be optimized using longer needles. Skinfold thickness can be a good marker to determine appropriate needle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The amplitudes were significantly higher when recording mTc-MEPs with subcutaneous needle electrodes compared to amplitudes recorded with surface electrodes. This corresponds with the intra-operative findings of other studies [ 13 , 19 ]. Gonzalez et al showed that recordings from intramuscular electrodes have significantly higher amplitudes than subcutaneous electrodes [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The amplitudes were significantly higher when recording mTc-MEPs with subcutaneous needle electrodes compared to amplitudes recorded with surface electrodes. This corresponds with the intra-operative findings of other studies [ 13 , 19 ]. Gonzalez et al showed that recordings from intramuscular electrodes have significantly higher amplitudes than subcutaneous electrodes [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds with the intra-operative findings of other studies [ 13 , 19 ]. Gonzalez et al showed that recordings from intramuscular electrodes have significantly higher amplitudes than subcutaneous electrodes [ 13 ]. Journee et al found higher amplitudes with subcutaneous electrodes compared to surface electrodes in horses [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The aforementioned similarity of wave morphology is not present when comparing between im and em needle electrode recordings. Intramuscular EMGs differ markedly from extramuscular recordings due to the presence of polyphasic waves (Giroux and Lamontagne, 1990;Skinner et al, 2008;Gonzalez et al, 2018). Similarity of waveforms is essential for specific comparison of electrode qualities and to judge whether they are interchangeable and free from bias from differences between intramuscular and extramuscular characteristics.…”
Section: Similarity Of Myographic Recordings Between Sc Needle and Sumentioning
confidence: 99%
“…Extramuscular MEPs typically reflect electrical activity of many motor units representing a large population of motor neurons whereas characteristics of single motor neurons are filtered out. Therefore, em MEP recordings are appropriate for assessing the upper motor neuron function since these sense the integral activity of many axons of spinal motor tracts and interconnected neurons and are insensitive for the activity of individual lower motor neurons ( Skinner et al, 2008 ; Gonzalez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%